Experimental investigation on evaporation dynamics of sessile ethanol droplets on a heated substrate. (December 2020) - Ye, Shuang; Zhang, Li; Wu, Chun-Mei; Li, You-Rong; Liu, Qiu-Sheng
Highlights: Evaporation dynamics of sessile ethanol droplet on a heated substrate is observed. The evolution of thermal patterns with the droplet height is determined. One central cell is found due to marangoni effect at a high substrate temperature. Wave number of HTWs and temperature fluctuation raise with substrate temperature. The effect of liquid supplementation on the thermal patterns can be neglected. Evaporation rate decreases first, then raises with the decrease of droplet height. Abstract: In order to understand the evolution of thermal patterns and the effect of the thermal convection in the sessile droplet on the evaporation processes, a series of experimental investigations on evaporation dynamics of sessile ethanol droplets on a heated substrate were carried out based on the steady state evaporation method. The contact radius of the droplet on the substrate is fixed at 2.5 mm and the droplet height varies from 0.4 to 1.2 mm. Results indicate that with the decrease of the droplet height, the temperature distribution near the droplet center becomes nonuniform, and hydrothermal waves and Bénard-Marangoni cells appear in sequence. The effect of liquid supplementation on the thermal patterns can be neglected. With the raise of the substrate temperature, both the wave number of the thermal waves and the frequency of the temperature fluctuation near the contact line increase. Moreover, the evaporation rate decreases first, and then increases with the decrease of the droplet height. The enhancing thermal convection in the droplet can promote the evaporation process at a high substrate temperature.